TINJAUAN YURIDIS SANKSI PENGUNCIAN DAN PENCABUTAN PENTIL BAN OLEH DINAS PERHUBUNGAN BAGI PELANGGAR LALU LINTAS PARKIR DI BADAN JALAN DAN TROTOAR DI KOTA SAMARINDA TERHADAP PERATURAN DAERAH NOMOR 05 TAHUN 2015 - Wibowo, Madi Dwi Putra (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACTThe level of development and population of the city of Samarinda continues to grow. This caused the city of Samarinda become more crowded at places such as buildings, shops, to meet the complex needs of Samarinda society. Given the increasingly widespread places, the parking lot become lessen. There are utilization for the parking lot on the public road and on the sidewalk. In addition, office locations, both private and government caused traffic jam every day. This also because the employees use the area around the office to park their vehicles.The problem in this writing is how the application of penalty of locking and revoking the tire valve by the department of transportation to the violator of parking traffic on the sidewalk in the city of Samarinda has fulfilled the formal legal requirements as an act of execution and how is the legal procedure for those who do not receive locking penalty and removal of the tire nipple.The writing of this thesis uses the Normative Juridical and Sociological (Empirical) Juridical research methods, namely the method of research that uses libraries and laws and conducts field studies, namely conducting field observations and direct interviews. The research areas are the Juanda and Basuki Rahmat roads.Â Keywords: tire locking, discharge of tire nipple, parking